Impact of controlled sprouting of wheat kernels on bread baking performance - Ehmke, Laura C. (Kansas State University, 2017)
A laboratory-scale method for wheat germination was developed and used to compare hard red winter wheat varieties for sprout related attributes, activity, and whole wheat bread baking performance. WB 4458, WB Grainfield, LCS Mint, LCS Wizard, SY Monument, and T158 wheat varieties grown in three Kansas locations were germinated with the developed small-scale germination method and falling number values were compared. Byrd, Tam 204, and T158 were germinated with a scaled-up germination method aimed at generating samples in three falling number ranges of less than 120 seconds (low falling number and highly sprouted), 250±40 seconds (medium falling number), and 350±40 seconds (high falling number and low sprouting). Controls were un-germinated, sound (>400 seconds falling number), samples of each variety. The control whole grain and sprouted wheat was ground into flour. A mixograph was used to determine dough water absorption and mixing time. Whole wheat bread was made to determine bread volume, crumb characteristics, and bread texture. Overall there were few significant differences within each wheat variety for the different levels of germination. The only significant difference observed in all three varieties was that each highly sprouted grain (<120 seconds falling number) produced bread with significantly lower elasticity than the control within each variety, indicating that this level of germination produced a gummier bread. Elasticity was positively correlated with falling number (r=+0.71). A focused analysis on the Byrd variety compared the germinated samples to samples generated with added malted barley to the same falling number ranges. RVA analysis showed the gelatinization profiles for germinated and malted samples were similar within each falling number range. The highly and medium sprouted grain had significantly lower dough water absorption than the malted counterparts for those levels and the medium sprouted grain also had a lower mix time then the malted sample. There were no significant differences in bread volume, crumb characteristics, or bread texture except the highly sprouted grain had significantly lower elasticity than the control and the malted counterpart was not significantly different. In general, this experiment demonstrated that variety and germination conditions are important considerations in sprouting wheat and that whole wheat flour made from a wide range of germination levels produced quality bread that was not different from the control for most of the parameters investigated.
Keywords: Sprouted whole wheat bread; Germinated wheat; Baking; Falling number